Pengaruh Rendam Kaki dengan Air Hangat terhadap Kualitas Tidur Lansia di Wilayah Kerja Puskesmas Slawi - Zehan Xassiray Maleo; Tutik Rahayu; Apriliyani Yulianti Wuriningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Elderly individuals are a group vulnerable to sleep disorders, with over 50% of them reporting a decline in sleep quality. Sleep disturbances in the elderly can affect their quality of life, which in turn impacts their physical and mental health. One non-pharmacological intervention considered safe, simple, and effective for improving sleep quality in the elderly is foot soaking in warm water. This study aims to evaluate the effect of foot soaking in warm water on the sleep quality of elderly individuals in the working area of Slawi Health Center. The research design used was pre-experimental with a one-group pre-test post-test design. A total of 34 elderly participants were selected using total sampling technique. The intervention consisted of soaking feet in warm water at a temperature of 37°C–39°C for 10 minutes before sleep, conducted for three consecutive days. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data obtained were analyzed using Paired Sample T-test for normally distributed data. The results showed that the average sleep quality score before the intervention was 10.12, which decreased to 7.85 after the intervention. Statistical analysis showed a significant difference in the mean scores before and after the intervention with a significance value of 0.0001. This indicates that foot soaking in warm water significantly impacts the improvement of sleep quality in the elderly. This intervention can be recommended as an effective, practical, and easy-to-implement independent nursing action to improve sleep quality in the elderly. Based on these findings, foot soaking in warm water can be a good option to improve sleep quality in the elderly, especially in community healthcare services.